Intellectual Humility with Partial Application. - Di Ceglie, Roberto (Philosophia, 2022)
Intellectual humility plays a crucial role among intellectual virtues. It has attracted considerable attention from virtue epistemologists, who have offered a fair number of treatments. In this essay, I argue that, regardless of the difference among these treatments, they are beset by two problems: (1) they fall into a circular argument; (2) they fall into a self-referential contradiction. I then argue that a recent proposal by D. Pritchard allows us to avoid (1), but not (2). However, by combining this proposal with another reflection advanced by the same author while he discusses the Wittgensteinian notion of hinge commitments, it is possible to avoid (2). The thesis that emerges is that only a partial application of intellectual humility solves (2). Finally, I reinforce this thesis by rejecting an alternative solution to (2).